Akseptabilitas Draf Kriteria Baru Penentuan Kalender Hijriah Menurut Ahli Falak di Indonesia - Fadholi, Ahmad (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
In 2015 AD, 2016 AD, 2017 and 2017 there was a new discussion about the draft of new criteria for the determination of the Islamic calendar in Indonesia, namely the draft MUI criteria and the new draft criteria MABIMS, with the criteria of 3 degrees hilal height and 6.4 degree elongation. This criterion is deliberately made for the benefit and mutual agreement for the unification of the hijri calendar in Indonesia. It is hoped that the experts of the Islamic organizations in Indonesia will give their views and attitudes to the draft of new criteria to harmonize the criteria for